2016
DOI: 10.1017/jfm.2016.689
|View full text |Cite
|
Sign up to set email alerts
|

The influence of near-wall density and viscosity gradients on turbulence in channel flows

Abstract: The influence of near-wall density and viscosity gradients on near-wall turbulence in a channel are studied by means of Direct Numerical Simulation (DNS) of the low-Mach number approximation of the Navier-Stokes equations. Different constitutive relations for density ρ and viscosity µ as a function of temperature are used in order to mimic a wide range of fluid behaviours and to develop a generalised framework for studying turbulence modulations in variable property flows. Instead of scaling the velocity solel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 62 publications
11
124
0
Order By: Relevance
“…As shown in previous works [11,12,15,16,23,24,30], the semilocal wall coordinate y is effective in accommodating changes in viscous scales due to variable properties, thus providing a meaningful representation for the turbulent velocity statistics. Therefore, all wall-normal profiles are plotted as a function of y in the present work.…”
Section: Scalar Statisticsmentioning
confidence: 85%
See 4 more Smart Citations
“…As shown in previous works [11,12,15,16,23,24,30], the semilocal wall coordinate y is effective in accommodating changes in viscous scales due to variable properties, thus providing a meaningful representation for the turbulent velocity statistics. Therefore, all wall-normal profiles are plotted as a function of y in the present work.…”
Section: Scalar Statisticsmentioning
confidence: 85%
“…Patel et al [16] showed that the viscous stress h/Re τ (du vD /dy) collapses reasonably well when plotted as a function of y . For the near-wall constant stress layer, this collapse can be written in terms of the turbulent eddy viscosity μ t as…”
Section: Turbulent Prandtl Numbermentioning
confidence: 97%
See 3 more Smart Citations